Self-reactive CD4(+) T cells activated during viral-induced demyelination do not prevent clinical recovery - Savarin, Carine (J Neuroinflammation, 2015)
BACKGROUND: Microbial infections have been implicated in initiating and enhancing severity of autoimmune diseases including the demyelinating disease multiple sclerosis (MS). Nevertheless, the incidence of both acute and persisting viral infections without evidence of autoimmune sequelae suggests that this process is well controlled. The conditions promoting or stemming self-reactive (SR) T cells following viral-induced tissue damage thus need to be better defined. Using a non-fatal viral mouse model of encephalomyelitis associated with demyelination and disability, yet ultimate clinical improvement, this study set out to monitor uptake and presentation of endogenous myelin antigens, as well as induction and fate of SR T cells. METHODS: Activation and central nervous system (CNS) recruitment of myelin-specific CD4 T cells was analyzed by flow cytometry during encephalomyelitis induced by a glia tropic murine coronavirus. Potential antigen-presenting cells (APC) ingesting myelin were characterized by flow cytometry and their ability to activate SR T cells tested by co-culture with carboxyfluorescein succinimidyl ester (CFSE)-labeled myelin-specific CD4 T cells. Endogenous SR T cell kinetics was analyzed within both cervical lymph nodes and CNS by Enzyme-Linked ImmunoSpot (ELISPOT) following viral infection. RESULTS: The data demonstrate the presence of APC capable of activating SR T cells in both draining lymph nodes and the CNS temporally correlating with overt demyelination. While both the CNS-infiltrating myeloid population and microglia ingested myelin, only CNS-infiltrating APC were capable of presenting endogenous myelin antigen to SR T cells ex vivo. Finally, SR T cell activation from the endogenous T cell repertoire was most notable when infectious virus was controlled and paralleled myelin damage. Although SR T cell accumulation peaked in the persistently infected CNS during maximal demyelination, they were not preferentially retained. Their gradual decline, despite ongoing demyelination, suggested minimal re-stimulation and pathogenic function in vivo consistent with the lack of autoimmune symptoms. CONCLUSIONS: The results demonstrate the potential for CNS tissue destruction to induce and recruit SR T cells to the injury site and support a host suppressive mechanism limiting development of autoimmunity.